How Retirement Affects Mental Health, Cognitive Skills and Mortality; an Overview of Recent Empirical Evidence - Jan C. van Ours (Tinbergen Institute, 2022)
Retiring is an individual labor market transition that affects the personal life of the workers involved and sometimes the life of their partners. This paper presents an overview of recent studies on the effects of retirement on mental health, cognitive ability and mortality. The results are all over the place but on average it seems like at retirement mental health improves, cognitive skills deteriorate and mortality is not affected. However, there is substantial effect heterogeneity. The range of outcomes is partly related to heterogeneity in terms of personal characteristics, type of job, institutional arrangements, and whether retiring was voluntary or mandatory. The variation in empirical findings makes it hard to see the forest for the trees and advocate evidence-based retirement policies that take health effects into account. Nevertheless, introducing more individual flexibility in the timing of retirement is a worthwhile policy alternative since this seems to be unambiguously beneficial for the health of workers retiring.
Keywords: I14; J26; 330; Retirement; Mental health; Cognitive ability; Mortality